FAMILY MYDIDAE - Calhau, Júlia; Lamas, Carlos José Einicker (Zootaxa, 2016)
Mydidae (Diptera, Asiloidea) are a relatively rare group of flies, and the knowledge on the Colombian mydids is very poor. According to available literature, only two species are registered to this country, Protomydas coerulescens (Olivier, 1811) and P. rubidapex (Wiedemann, 1830).